2011
DOI: 10.1089/end.2010.0591
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Catheters May Be Superior to Latex Catheters in Difficult Urethral Catheterization After Urethral Dilation

Abstract: In the setting of the difficult urethral catheterization, silicone catheters should be used after urethral dilation, advanced through a Glidewire, because they offer more resistance to buckling and might necessitate less dilation than conventional latex catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Based on tensile strength of commercial Foley catheter brands (6–8 MPa), the 3D-printed silicone prints evaluated in this study demonstrated similar strength (7.28 MPa) (Figure C). A comparable tensile strength of 6.29 MPa has been reported for 12 Fr silicone urinary catheters currently in use in patients . Although L.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Based on tensile strength of commercial Foley catheter brands (6–8 MPa), the 3D-printed silicone prints evaluated in this study demonstrated similar strength (7.28 MPa) (Figure C). A comparable tensile strength of 6.29 MPa has been reported for 12 Fr silicone urinary catheters currently in use in patients . Although L.…”
Section: Discussionsupporting
confidence: 68%
“…A comparable tensile strength of 6.29 MPa has been reported for 12 Fr silicone urinary catheters currently in use in patients. 53 Although L. rhamnosus-containing material exhibited lower strength (2.2 MPa), this value was in the range of aged Foley catheters (2−5 MPa). 52 The value was also similar to the tensile strength of 2.7 MPa for 12 Fr latex urinary catheters used in patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…described the superior stiffness of silicone catheters in the setting of urethral dilation. 11 This propensity not to kink makes them easier to insert. Nacey et al .…”
Section: Discussionmentioning
confidence: 99%